Myocardial injury in spontaneous intracerebral hemorrhage is not predicted by prior cardiac disease or neurological status: results from the Mannheim Stroke database - Lesch, Hendrik; Haucke, Lea; Kruska, Mathieu; Ebert, Anne; Becker, Louisa; Szabo, Kristina; Akın, Ibrahim; Alonso, Angelika; Fastner, Christian (Frontiers in neurology, 2025)
Background and aimsElevated cardiac troponin (cTn) levels (representing myocardial injury) are frequently found in patients with spontaneous intracerebral hemorrhage (sICH). Overall, the relationship between sICH and elevated cTn levels is not well understood. The aim of this study was to investigate patient characteristics and clinical parameters in patients with sICH and myocardial injury.MethodsThis is a retrospective observational study based on the Mannheim Stroke database. Consecutive patient cases with acute symptomatic sICH and available high-sensitivity cTn I (hs-cTnI) at hospital admission between 2015 and 2021 were included. Group comparisons of patient, clinical and imaging characteristics were performed between groups with and without hs-cTnI elevation. In addition, variables with suspected predictive clinical significance for hs-cTnI elevation were analyzed for their predictive value using multivariate logistic regression analysis.ResultsA total of 93/498 patients with sICH (18.7%; mean age 73 ± 15 years; 51.9% females) had a hs-cTnI elevation. These patients did not have a more pronounced cerebrovascular risk profile and had a comparably low prevalence of coronary artery disease (18.5%, p = NS) compared to those without elevated hs-cTnI levels. Elevated hs-cTnI levels had no impact on in-hospital mortality (21.5 vs. 20.5%, p = NS) or functional outcome at discharge. Solely clinically relevant aortic valve stenosis, graded as moderate or higher, independently predicted hs-cTnI elevation (p < 0.003). Other cardiac preconditions or neurological functional parameters did not serve as significant predictors.ConclusionsMyocardial injury is common in patients with sICH. Unlike in AIS patients, elevated hs-cTnI levels were not associated with a worse functional or mortality-related in-hospital outcome. Except for clinically relevant aortic valve stenosis, structural heart disease had no significant influence as a predictor. We therefore suggest that hs-cTnI elevation in patients with sICH is related to acute myocardial damage along the brain-heart axis.
Gesehen am 15.07.2025